Index of mathematics learning activities suitability to learners - Kurilova, Julija; Kurilovas, Eugenijus (Lietuvos matematikos rinkinys, 2016)
The paper aims to present an original probabilistic method to creating personalised learning activities and units. The method is based on evaluating learning components suitability to students needs according to their learning styles. In the paper, Felder–Silverman Learning Styles Model and Inquiry Based Learning method suitable to learn Math are used. Expert evaluation method based on Trapezoidal Fuzzy Numbers theory is applied in the research to obtain numerical values of suitability of IBL activities to students learning styles. Personalised learning units should consist of learning components (i.e. learning activities) that are optimal (i.e. the most suitable) to particular students according to their learning styles. Optimal means having the highest suitability index. In the paper, this original probabilistic method is applied to establish probabilistic suitability of IBL activities to particular students.